Aisha Bint Abu Bakr And Her Contributions To Hadith Transmission And Islamic Education In Early Islamic History - Fadilah Balqis; Sulia Cika Aulia; Annisa Nurwahidah Larasati; Putri Octaviana; Mustika Sari’ah Siagian (PT Ilmu Data Indonesia, 2026)
Aisha bint Abu Bakr was one of the most influential female figures in Islamic history, making significant contributions to scholarship, education, and the transmission of the Prophet Muhammad's traditions. This study aims to examine the biography, role, and contributions of Aisha bint Abu Bakr in the development of Islamic civilization. The research employs a library research method with a descriptive qualitative approach by analyzing various literature sources, including hadith collections, Islamic historical works, and relevant scholarly articles. The findings indicate that Aisha was not only known as the wife of the Prophet Muhammad but also as a distinguished female scholar recognized for her intelligence, accuracy, and strong intellectual capacity. She narrated thousands of prophetic traditions that became essential references in Islamic law, ethics, worship, and social life. Furthermore, Aisha played an active role in educating the Muslim community by teaching religious knowledge to companions and subsequent generations. Her contribution to preserving and disseminating Islamic teachings established her as one of the primary sources of Islamic knowledge during the early Islamic period. This study concludes that Aisha bint Abu Bakr holds a highly significant position in Islamic history as a prominent female figure who influenced scholarship, education, and the transmission of Islamic teachings.